1998
DOI: 10.1021/jm970860z
|View full text |Cite
|
Sign up to set email alerts
|

Structure−Activity Relationship of New Growth Inhibitors of Trypanosoma cruzi

Abstract: Several drugs bearing the 4-phenoxyphenoxy skeleton and other closely related structures were designed, synthesized, and evaluated as antiproliferative agents against Trypanosoma cruzi, the etiologic agent of Chagas' disease. The new class of drugs was envisioned by modifying the nonpolar 4-phenoxyphenoxy moiety replacing selected aromatic protons by different groups via electrophilic aromatic substitution reactions as well as introducing a sulfur atom at the polar extreme. Of the designed compounds, sulfur-co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
77
2

Year Published

1999
1999
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 50 publications
(82 citation statements)
references
References 38 publications
(141 reference statements)
3
77
2
Order By: Relevance
“…Only the Mexican strain H1 was resistant to both drugs, according to the criteria established in previous studies, because it had IC 50 G and IC 50 M values higher than 50 lM (Nirdé et al 1995, Villarreal et al 2005. The IC 50 M and IC 50 G values for the other Mexican strains were heterogeneous, and they were comparable with values reported for South American strains, such as Tulahuen 2 (TcIV), Dm28c (TcI), Silvio (TcI), Esmeraldo (TcII), and Y (TcII) (Cinque et al 1998, Vieites et al 2008, Wilkinson et al 2008, Luna et al 2009.…”
Section: Discussionsupporting
confidence: 59%
“…Only the Mexican strain H1 was resistant to both drugs, according to the criteria established in previous studies, because it had IC 50 G and IC 50 M values higher than 50 lM (Nirdé et al 1995, Villarreal et al 2005. The IC 50 M and IC 50 G values for the other Mexican strains were heterogeneous, and they were comparable with values reported for South American strains, such as Tulahuen 2 (TcIV), Dm28c (TcI), Silvio (TcI), Esmeraldo (TcII), and Y (TcII) (Cinque et al 1998, Vieites et al 2008, Wilkinson et al 2008, Luna et al 2009.…”
Section: Discussionsupporting
confidence: 59%
“…Fenoxycarb and analogs were synthesized, and assays with epimastigotes suggested that an allyl ether moiety bonded at the polar extreme is important for the trypanocidal effect (Cinque et al 1998). Some analogs were also active against bloodstream forms and reduced the parasitemia and mortality levels in relation to untreated controls (Fichera et al 1995).…”
Section: Drugs Derived From Natural Sourcesmentioning
confidence: 99%
“…9 Their efficacy is also limited to the acute phase of the infection, and it is highly variable so that there is still controversial evidence that patients really benefit from such treatments. 10 A variety of new drugs is thus currently under development, [20][21][22][23][24] and some appear to show promise. However, additional studies are necessary and it will be some time before new treatments become available.…”
Section: Overview Of the Diseasementioning
confidence: 99%